Measuring and Modeling of P- and S-Wave Velocities on Crustal Rocks: A Key for the Interpretation of Seismic Reflection and Refraction Data - Hartmut Kern (International Journal of Geophysics)
Lithologic interpretations of the earth crust from seismic wave velocities are non-unique so that inferences about composition can not be drawn. In order to evaluate how elastic properties of rock materials are controlled by lithology at in situ pressures and temperatures, compressional (Vp), shear wave velocities (Vs) and velocity anisotropy of crustal rocks were measured at conditions of greater depth. The first part deals with the interdependence of elastic wave propagation and the physical and lithological parameters. In the second part data from laboratory seismic measurements and theoretical calculations are used to interpret (1) a shallow seismic reflection line (SE Finland) and (2) a refraction profile of a deep crust (Central China). The comparison of the calculated velocities with the experimentally-derived in situ velocities of the Finnish crustal rocks give hints that microcracks have an important bearing on the in situ seismic velocities, velocity anisotropy and the reflectivity observed at relative shallow depth. The coupling of the experimentally-derived in situ velocities of P- and S-wave and corresponding Poisson's ratios of relevant exhumed high-grade metamorphic crustal rocks from Central China with respective data from seismic refraction profiling provided a key for the lithologic interpretation of a deep seismic crustal structure.